2012
DOI: 10.1126/scitranslmed.3003578
|View full text |Cite
|
Sign up to set email alerts
|

Cell Carriage, Delivery, and Selective Replication of an Oncolytic Virus in Tumor in Patients

Abstract: Oncolytic viruses, which preferentially lyse cancer cells and stimulate an antitumor immune response, represent a promising approach to the treatment of cancer. However, how they evade the antiviral immune response and their selective delivery to, and replication in, tumor over normal tissue has not been investigated in humans. Here,we treated patients with a single cycle of intravenous reovirus before planned surgery to resect colorectal cancer metastases in the liver. Tracking the viral genome in the circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(169 citation statements)
references
References 24 publications
6
160
1
2
Order By: Relevance
“…Innate immunity and complement may impede delivery of oncolytic viruses, especially with the intravenous approach (27). However, transportation by cells may also protect virus during intravenous delivery, despite the presence of neutralizing antibodies prior to infusion (28). The role of adaptive immunity in limiting the benefit of repeated administrations of virus is unknown and requires additional study.…”
Section: Discussionmentioning
confidence: 99%
“…Innate immunity and complement may impede delivery of oncolytic viruses, especially with the intravenous approach (27). However, transportation by cells may also protect virus during intravenous delivery, despite the presence of neutralizing antibodies prior to infusion (28). The role of adaptive immunity in limiting the benefit of repeated administrations of virus is unknown and requires additional study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two clinical studies have demonstrated that certain OVs can be delivered to tumor beds despite the presence of some level of circulating antibody (47,48). Nevertheless, it is widely believed that nAbs that arise during therapy will significantly abrogate therapeutic efficacy of repeated systemic OV applications (13,49).…”
Section: Discussionmentioning
confidence: 99%
“…In both preclinical and clinical studies, it is clear that a robust and specific infection of tumor bed oncolytic viruses is achievable after intravenous infusion or i.t. injection using various platforms [101][102][103]. I.t.…”
Section: Combining Checkpoint Inhibition With Oncolytic Viruses (T-vec)mentioning
confidence: 99%